What is the equation of the line that passes through (1, 3) and (-2, -3)?

Question

Asked 3/13/2014 6:14:17 AM

Updated 3/13/2014 7:21:49 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/13/2014 7:15:51 AM]

andrewpallarca|Points 32954|

vonna79|Points 598|

Question

Asked 3/13/2014 6:14:17 AM

Updated 3/13/2014 7:21:49 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [3/13/2014 7:15:51 AM]

Rating

3

The equation of the line that passes through (1, 3) and (-2, -3) Is y = 2x + 1

Added 3/13/2014 7:17:02 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/13/2014 7:19:41 AM]

3

(12x^2 - 10x -12) ÷ (3x + 2)

= [(4x - 6)(3x + 2)]/(3x + 2)

= 4x - 6

= [(4x - 6)(3x + 2)]/(3x + 2)

= 4x - 6

Added 3/13/2014 7:21:49 AM

Input in standard form the equation of the given line.
The line with m = 1/2 and b = 3.

Question

Not Answered

Updated 3/6/2014 8:18:47 AM

1 Answer/Comment

The line with m = 1/2 and b = 3 in standard form is x - 2y = - 6

Added 3/6/2014 8:18:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:27 AM]

Find the solution to the equations.
2x - y = -3
x + y = 0
(0, 0),
(-1, 1),
(1, -1), **Weegy:** A.(0, 0) is the answer. x=0, y=0 **User:** 5x + 10y = 18
x = y - 6
Which of the following equations is the result of substituting y - 6 in for x in the first equation?
5x + 10y - 6 = 18,
5y - 6 + 10y = 18,
5y - 30 + 10y = 18, (More)

Question

Expert Answered

Updated 3/10/2014 8:08:23 AM

2 Answers/Comments

The solution to the equations 2x - y = -3, x + y = 0 is (-1, 1).

Added 3/10/2014 7:52:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:31 AM]

5x + 10y = 18

x = y - 6, replace x in the first equation we get:

5(y - 6) + 10y = 18

so, the result of substituting y - 6 in for x in the first equation is 5y - 30 + 10y = 18

x = y - 6, replace x in the first equation we get:

5(y - 6) + 10y = 18

so, the result of substituting y - 6 in for x in the first equation is 5y - 30 + 10y = 18

Added 3/10/2014 8:08:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:30 AM]

factor 14a2 - 68a + 48

Question

Not Answered

Updated 3/10/2014 7:08:41 AM

1 Answer/Comment

The factored form of 14a2 - 68a + 48 is:

2(7a - 6)(a - 4)

2(7a - 6)(a - 4)

Added 3/10/2014 7:08:41 AM

This answer has been confirmed as correct and helpful.

What is the slope of the line 4x + 6y = 12?

Question

Not Answered

Updated 3/13/2014 7:43:41 AM

2 Answers/Comments

The slope of the line 4x + 6y = 12 is -2/3.

Added 3/13/2014 7:43:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/14/2014 8:32:17 AM]

Solve each equation.
(x + 3)(x - 3) = 16 - 2x2 **Weegy:** x - 5 = 10 x = 10 + 5 x = 15 (More)

Question

Expert Answered

Updated 3/17/2014 7:28:53 AM

1 Answer/Comment

(x + 3)(x - 3) = 16 - 2x^2

x^2 - 9 = 16 - 2x^2

3x^2 = 25

x^2 = 25/3

x = +/- sqrt(25/3)

= +/- 5/sqrt3

= +/-(5sqrt3)/3

x^2 - 9 = 16 - 2x^2

3x^2 = 25

x^2 = 25/3

x = +/- sqrt(25/3)

= +/- 5/sqrt3

= +/-(5sqrt3)/3

Added 3/17/2014 7:28:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/17/2014 7:32:18 AM]

27,935,127

questions answered

There are no comments.